Development of Point Counter Point-Based Teaching Materials To Increase Speaking Ability in Debate Material for Student of Darul Hikmah Islamic Boarding School in Asahan - Irhami Tanjung, Syahri; Rahmat Kartolo; Sutikno (PT Inovasi Pratama Internasional, 2026)
This study aims to determine the Development of Teaching Materials Based onPoint Counter Point to Improve Speaking Ability in Debate Material in Class X Students of Madrasah Aliyah Pesantren Darul Hikmah Asahan Academic Year 2025/2026. This type of research is experimental research with Random Sampling. The population in this study was the entire class X which amounted to 30 students. The sample of this study amounted to 30 students divided into 6 groups, namely group I consisting of 5 students as a control class using the conventional model and group II consisting of 5 students using the Point Counter Point model. The technique used in determining the sample is a simple Random Sampling technique. The instrument used in data collection is an essay test. After the learning was completed, a post-test was obtained with an average result of the experimental class of 88.13 and the control class of 80. The results of the t-test obtained tcount = 5.60> ttable = 2.00, so the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, there is a Development of Point Counter Point Based Teaching Materials to Improve Debate Speaking Skills in Class X Students of Madrasah Aliyah Pesantren Darul Hikmah in the 2025/2026 Academic Year